Abordaje quirúrgico odontológico en un paciente con displasia cleidocraneal: Reporte de caso (2023)
Cleidocranial dysplasia (CCD) is a rare genetic disease that compromises normal bone development, caused by the alteration in the RUNX2 gene of chromosome 6p (short arm), has as consequences severe bone alterations due to anomalies in intramembranous ossification that, in turn, lead to modifications in the development of cranial and clavicular bones, multiple effects on the number, eruption and replacement of teeth, and functional difficulties, as well as changes in psychosocial behavior due to deterioration in the quality of life. Objective: To study and evaluate the present case of a patient with Cleidocranial Dysplasia in order to suggest an approach taking into account the review of the literature. Methods and Materials: Corresponds to a case study of a 10 year old male patient with cleidocranial dysplasia, born (02/04/2012) by cesarean section at the Departmental Hospital San Antonio De Pitalito, with initial weight of 4.8 kg and 54 cm in height, the initial medical and semiological diagnosis describes the presence of wide and normotensive anterior fontanel, pink conjunctival eyes, moist oral mucosa, normal bilateral otoscopy, normal neck. Results: Surgery was performed in the lower jaw, extractions of primary teeth 83,82,81,71,72,73 and supernumerary teeth in the area of these extractions which were 5 supernumerary teeth, followed by operculectomy of teeth 46 and 36. Conclusion: The intervention plan accompanied by the psychological process allowed a complete process of acceptance and interest of the patient to improve his condition; The guided eruption allows to bring permanent teeth to the occlusal plane, allowing to perform the lower and upper jaw surgery followed by a strict post surgical control.